Optimizing the Value of Goat Manure as Organic Fertilizer Through Anaerobic Processing and Enhanced E-Commerce Marketing - Wijayanti, Dwi; Hikmatyar, Missi; Rahwana, Kusuma Agdhi; Fadillah, Muhammad Gustyar; Kasyfurrahman, Muhammad Akbar; Nugraha, Erin Fajrin; Sacadiraksa, Widia (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Dairy goat farming is a livestock system in which all goat-derived products, including milk, meat, urine, and feces, can be utilized. At Pure Fresh Dairy Farm, more than 120 dairy goats produced a significant amount of milk. However, the large goat population also generated substantial amounts of feces. Prior to this initiative, there had been no utilization or processing of goat feces using anaerobic technology to produce organic fertilizer or generate additional farm income. This community service program aimed to provide knowledge and training to Pure Fresh on producing organic fertilizer from dairy goat feces using the anaerobic method and enhancing its market value through e-commerce. The organic fertilizer was produced using dairy goat feces combined with dolomite lime, molasses, and EM4. The addition of these components accelerated the fermentation process, enhanced efficiency, and resulted in a higherquality fertilizer with a more balanced nutrient composition, thereby improving soil conditions. The fertilizer products were marketed to supplement Pure Fresh’s income, while a portion was allocated for community agricultural use. The final product was packaged in transparent plastic bags weighing 2 kg, branded as ‘PO-GOAT’. The initial production yielded 54 kg, which was sold at IDR10,000 per 2 kg and was planned to be marketed through e-commerce.